Chapter 1 Introduction On Soviet Intellectual Culture during the Stalin Era - Viljanen, Elina (Taylor & Francis, 2023)
The authors of our book focus on Soviet scholars and cultural theoreticians during the Stalin era from a methodological perspective that distinguishes between Stalinism and culture, an outlook that forms one of the common threads of the book. This introductory chapter focuses on the theoretical grounding of this approach. We argue that the received picture of Soviet culture in general and of Stalin era culture in particular has yet to be fully disentangled from the political and historical narratives of the Cold War epoch, especially with respect to the persistent traits of totalitarianism theory in defining Stalinism. The point of departure from the still dominant 'revisionist' model of Soviet historiography involves the proposition that Stalin's brand of totalitarianism was a collective cultural product. Our book in turn revises this thesis by claiming that Stalin rarely sought to control culture in a totalitarian manner. He was aware of the limits of control over culture. Meanwhile, society in general and notable cultural actors in particular need to be contextualised and theorised as political subjects from various points of view. Stalinism was a phenomenon that was organically embedded in the culture of the era - thus the metaphor of a 'parasite' seems to describe this relationship in a more adequate manner Stalin era intellectuals can be viewed as cultural actors who adopted different 'patriotic' strategies from the political arena to gain some level of autonomy that enabled to them to function in their fields. These strategies ensured that certain theoretical ideas were able to persist despite major political campaigns.